Detection of Deltacoronavirus in environmental fecal samples from seabirds in the Saint Peter and Saint Paul Archipelago, central equatorial Atlantic Ocean - Fernanda Gomes; Alexandre Freitas da Silva; Tatiana Prado; Marina Galvão Bueno; Luciana Appolinario; Patrícia Soares Flores; Paola Cristina Resende; Marilda Siqueira; Leonardo Corrêa; Martha Brandão; Jose Reck; Gabriel Luz Wallau; et al. (PLoS ONE, 2025)
This study investigates the presence of avian coronaviruses (CoVs), Avian influenza viruses (AIVs), and Avian rotaviruses group A (AvRVs) in seabird populations inhabiting the Saint Peter and Saint Paul Archipelago (SPSPA), isolated and remote oceanic islands situated in the equatorial region of the Atlantic Ocean. In July 2022, 95 environmental fecal samples were collected from seabird colonies and screened for these viruses by quantitative one-step real-time RT-PCR (AIVs and AvRVs), by the conventional pancoronavirus RT-PCR protocols and metatranscriptomics of a positive sample. Four environmental samples tested positive for CoVs. Avian AIVs and AvRVs were not detected. Phylogenetic analyses revealed CoVs closely related to avian deltacoronaviruses previously identified in waterbirds from Asia and Australia. We could not recover the CoV by metatranscriptomics but we recovered a single viral contig of an avian enterovirus. The findings contribute valuable insights into virus dynamics among seabird populations, laying the groundwork for future investigations in this field.